Manajemen Sumber Daya Manusia dalam Upaya Peningkatan Mutu Guru di SMK Ma’arif NU 1 Kembaran Banyumas - Agus Sunarso (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2020)
This research is based on the importance of human resource management in a school. In this regard, this study aims to determine Human Resource Management in Efforts to Improve Teacher Quality at SMK Maarif NU 1 Kembaran Banyumas. This research is a qualitative research. Data collection used interviews, observation, and documentation, and the validity of the data used triangulation, and data analysis techniques included data collection, data reduction, data presentation, and drawing conclusions. This research resulted in four conclusions: (1) Human resource planning carried out at SMK Ma'arif NU 1 Kembaran Banyumas, namely by analyzing the volume and workload, then analyzing the strengths and weaknesses of the school's workforce. The school's financial capacity for operational costs, infrastructure and monthly expenses such as electricity, infrastructure maintenance and honoraria are also important things to consider. (2) Recruitment, selection and placement of human resources at SMK Ma'arif NU 1 Kembaran Banyumas are divided into 2, namely recruitment, selection and placement of workers from internal and external sources. (3) Training and Development of Human Resources at SMK Ma'arif NU 1 Kembaran Banyumas, namely by using two approaches, namely training carried out in the workplace (On The Job Training) and Training carried out outside the workplace (Off The Job Training) . (4) The evaluation or assessment carried out at SMK Ma'arif NU 1 Kembaran, Banyumas Regency is an annual system, namely an evaluation that is carried out once every year. The evaluation implemented at SMK Ma'arif NU 1 Kembaran Banyumas is supervision activities (class to class visits) by the school principal and the team appointed as the assessment team, namely the deputy principal.